A counterfactual decomposition analysis of immigrants-natives earnings in Malaysia - Muhammad Anees; Muhammad Sajjad; Ishfaq Ahmed (Kiel Institute for the World Economy (IfW), 2011)
Economics of discrimination has been the topic of interest of many in the last decade or two. Human capital theory describes wage determination as a function of labour human capital and should be determined based on marginal productivity theorem of labour economics. Islamic theology also dictates paying labour well in time and equal to their productivity not based on his colour, race, gender, nationality health status and other non-economic factors. The current study analyses the immigrants-natives wage gap to find the extent of potential discrimination against the immigrants. Using employees' level data from the Enterprise Surveys by the World Bank in 2007, standard Oaxaca-Blinder technique and Machado-Mata counterfactual decomposition is applied. Findings indicate an existence of earning's differential in favour of natives or the Malaysian citizens and immigrants have a disadvantage. On the other hand, the differential increases until the middle of income distribution and the start declining. It suggests higher-income groups have a low level of discriminatory disadvantage. Labour market productivity could be increased if this differential is reduced, which motivates the employees.
Keywords: J; J1; J3; J7; 330; Labour market discrimination; Oaxaca-Blinder decomposition; Machado-Mata decomposition; quantile regression; earnings differential; enterprise survey; World Bank; Malaysia